2004
DOI: 10.1002/jbm.b.30014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro tobramycin elution analysis from a novel β‐tricalcium phosphate–silicate‐xerogel biodegradable drug‐delivery system

Abstract: This in vitro research analyzed local tobramycin elution characteristics from a novel, biodegradable drug delivery system, consisting of a beta-TCP bone substitute, VITOSS trade mark, encapsulated with silicate xerogel prepared by the sol-gel process. Tobramycin elution from silicate-xerogel-encapsulated VITOSS was compared directly with non-silicate-xerogel-encapsulated VITOSS to assess whether xerogels are effective in delivering greater tobramycin quantities in a controllable, sustained manner crucial for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…Our results for aqueous-impregnated TCP samples are consistent with results of the study using tobramycin by DiCicco et al 9 As shown in Figure 2, only trace amounts of antibiotic are released after 2 days. This is likely due to the mechanism of gentamicin incorporation into the scaffold.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Our results for aqueous-impregnated TCP samples are consistent with results of the study using tobramycin by DiCicco et al 9 As shown in Figure 2, only trace amounts of antibiotic are released after 2 days. This is likely due to the mechanism of gentamicin incorporation into the scaffold.…”
supporting
confidence: 92%
“…Initial first order kinetics were noted previously in the literature for tobramycin elution from TCP. 9 Thus, the elution rate is proportional to the concentration of gentamicin remaining in the implant, consistent with egress controlled by diffusion.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…[140143] The incorporation of other degradable particles such as poly(trimethyl carbonate) and gelatin microparticles has yielded similar favorable results within injectable formulations, [144, 145] and the potential for drug or growth factor release from these systems has been well demonstrated. [146150] Including a water soluble porogen such as mannitol can both improve the injectability of CaP cement while also improving the flexural strength and toughness of the resulting scaffold. [151] Although not part of an injectable system, the incorporation of an absorbable polymer mesh within a CaP cement can also significantly increase the flexural strength and toughness of the material while resulting in macroporosity upon degradation of the network.…”
Section: Injectable Scaffoldsmentioning
confidence: 99%